Urine exosomes as biomarkers in bladder cancer diagnosis and prognosis: From functional roles to clinical significance - Lee, Nicholas; Canagasingham, Ashan; Bajaj, Mohit; Shanmugasundaram, Ramesh; Hutton, Anthony; Bucci, Joseph; Graham, Peter; Thompson, James; Ni, Jie (Frontiers in Oncology, 2022)
Bladder cancer is one of the top ten most common cancers and top ten causes of cancer death globally. 5-year survival rates have decreased in Australia from 66% to 55% in the past three decades. The current gold standard for diagnosis is cystoscopy. However, cystoscopies are an invasive and health-resource intensive procedure which has sub-optimal sensitivity for flat lesions such as CIS (carcinoma in situ) and low specificity for differentiating inflammation from cancer - hence requiring biopsies under anaesthesia. Frequent and life-long surveillance cystoscopy is required for most patients since there are high rates of progression and local recurrence in high-risk non-muscle invasive cancer (NMIBC) as well as poor outcomes associated with delayed detection of muscle-invasive bladder cancer (MIBC). There is an unmet need for a non-invasive test to provide better discrimination and risk-stratification of bladder cancer which could aid clinicians by improving patient selection for cystoscopy; enhanced risk stratification methods may guide the frequency of surveillance cystoscopies and inform treatment choices. Exosomes, which are nano-sized extracellular vesicles containing genetic material and proteins, have been shown to have functional roles in the development and progression of bladder cancer. Exosomes have also been demonstrated to be a robust source of potential biomarkers for bladder cancer diagnosis and prognosis and may also have roles as therapeutic agents. In this review, we summarise the latest evidence of biological roles of exosomes in bladder cancer and highlight their clinical significance in bladder cancer diagnosis, surveillance and treatment.